Particularity, Incarnation, and Discernment: Bonhoeffer’s "Christmas" Spirituality - Dahill, Lisa E. (Studies in Christian-Jewish Relations, 2011)
Dietrich Bonhoeffer has a “Christmas” spirituality, an incarnate spirituality immersed in the complexity and particularity and messiness of the world â where the God who becomes flesh lives. In his writings he is not primarily interested in the triumph of Easter but in the deepening incarnation precisely into God’s own poverty, darkness, emptiness â and joy, mercy, sweetness, love â met for Christians in Jesus Christ. In a world today where Christians in our context too often tend to see ourselves in the place of the victor, the divine agent, the conqueror in the name of “God,” his is a refreshingly humble and open perception of divine reality, curious about the world as it is and eager to find precisely in the faces and alterity of every other the very face of God.